Kidney histopathology of white rats (Rattus norvegicus) fed a high-fat diet, curcumin supplement, and turmeric powder (Curcuma longa) - Tyas Rini Saraswati; Nur Exmah; Silvana Tana (Department of Biology, Faculty of Sci and Tech, Universitas Islam Negeri Alauddin Makassar, 2022)
.